A Versatile Analytical Method of Investigating MMF Harmonics of Armature Windings - Ze-Zheng Wu; Jian-Xin Shen (IEEE Access, 2023)
Analytical methods are of great interest for the design and analysis of AC machines. This paper proposes a new analytical method to study the harmonic rotating components of the magneto motive force (MMF) produced by various types of armature windings and input currents. The windings can be symmetrical-phase or asymmetrical-phase, single-layer or multi-layer, fractional-slot or integer-slot, with arbitrary phase numbers. The analytical method is expressed as concise steps and closed-form equations, and its validity and reliability are verified by comparison to finite element analysis (FEA) simulations and experiments. As opposed to previous works, the proposed method establishes a more comprehensive quantitative relationship among the harmonics of the resultant MMF, the arrangement of armature windings, and the input currents. Practical implications of this method include enabling more accurate prediction of machine performance, as well as optimizing machine design in both quantitative and qualitative respects.